#TITLE_ALTERNATIVE# - HENDRIONO (NIM : 15011018), LEONARDO
The rapid growth of human population demands quick availability for adequate housing. This problem drive advances in construction technology towards instant building system. One of the primary concerns in present is prefabricated system, especially modular housing. However applications of these technologies are rare to be found in earthquake-prone countries, especially Indonesia. Therefore, this study focuses on analyzing seismic performance of low-rise apartment in Bandung with cold-formed steel modular construction. This study starts with modeling stage by utilizing ETABS 9.7.4 software. The structure model has a total dimension of 14 x 40 m which is composed by 16 pairs of modules measuring 2.5 x 6 m and a 2 m wide corridor that runs along the center of the building. Total number of floors is planned to be 6 with 3 m heights for each floor. The modular structure is designed using seismic resistant system in the form of bearing wall that consists of a lightweight frame (cold-formed steel) and wood infill panels for shear. All of those structural elements are designed with performance-based design method. Regulations used for design refer to SNI 1726-2012 and AISC 41-13. Analysis is divided into two methods to review the seismic performance of structure, Pushover Analysis and Linear Time History Analysis. Pushover analysis devised static lateral load to be given until the building reaches the point of collapse. Results from pushover will be evaluated for structural performance level and value. While linear time history analysis used real seismic data of EL CENTRO 1940, to determine the elastic capacity of the structure.